Exceptional Cycling Performance Enabled by Local Structural Rearrangements in Disordered Rocksalt Cathodes. Issue 27 (23rd May 2022) - Ahn, Juhyeon; Ha, Yang; Satish, Rohit; Giovine, Raynald; Li, Linze; Liu, Jue; Wang, Chongmin; Clement, Raphaele J.; Kostecki, Robert; Yang, Wanli; Chen, Guoying
Abstract: The capacity of lithium transition‐metal (TM) oxide cathodes is directly linked to the magnitude and accessibility of the redox reservoir associated with TM cations and/or oxygen anions, which traditionally decreases with cycling as a result of chemical, structural, or mechanical fatigue. Here, it is shown that a capacity increase over 125% can be achieved upon cycling of high‐energy Mn‐ and F‐rich cation‐disordered rocksalt oxyfluoride cathodes. This study reveals that in Li1.2 Mn0.7 Nb0.1 O1.8 F0.2, repeated Li extraction/reinsertion utilizing Mn 3+ /Mn 4+ redox along with some degree of O‐redox participation leads to local structural rearrangements and formation of domains with off‐stoichiometry spinel‐like features. The effective integration of these local "structure‐domains" within the cubic disordered rocksalt framework promotes better Li diffusion and improves material utilization, consequently increased capacity upon cycling. This study provides important new insights into materials design strategies to further exploit the rich compositional and structural space of Mn chemistry for developing sustainable, high‐energy cathode materials. Abstract : The intrinsic changes associated with voltage and capacity evolution upon cycling of cation‐disordered Mn‐rich oxyfluoride rocksalt cathode are investigated. Detailed diagnostic studies reveal the formation of local off‐stoichiometry spinel‐like domains accompanying reversible Mn and O redox, resulting in better Li diffusion kinetics and improved material utilization of the cathode active material.